Trends in assisted ventilation and outcome for obstructive pulmonary disease exacerbations. A nationwide study. - Anne Pernille Toft-Petersen; Christian Torp-Pedersen; Ulla Møller Weinreich; Bodil Steen Rasmussen (PLoS ONE)
Background Non-invasive ventilation (NIV) has been used for decades in treatment of exacerbations of chronic obstructive pulmonary disease (COPD). The impact of the changing use of assisted ventilation in acute exacerbations on outcomes has not been fully elucidated and we aimed to describe these changes in the Danish population and describe their consequences for mortality. Methods A register-based study was conducted of a cohort of 12,847 patients admitted for acute exacerbation of COPD (AECOPD) from 2004 through 2011, treated with invasive mechanical ventilation (IMV) or NIV for the first time. Age, sex, in-hospital mortality rates, time to death or readmission for AECOPD were established and changes over time tracked. Results The number of admissions for AECOPD where assisted ventilation was used was 1,130 in 2004 and had increased by 145% in 2011. First time ventilations increased by 88%. This was mainly due to an increase in use of NIV accounting for 36% of the total number of assisted ventilations in 2004 and 67% in 2011. The number of IMV with or without NIV treatments remained constant. The mean age of NIV patients increased from 71.5 to 73.6 years, but remained constant at 70.0 years in IMV patients. Mortality rates both in hospital and after discharge for patients receiving NIV remained constant throughout the period. In-hospital mortality following IMV increased from 30% to 38%, but mortality after discharge remained stable. Conclusion Assisted ventilation has been increasingly used in a broader spectrum of AECOPD patients since the introduction of NIV. The changes in treatment strategies have been followed by shifts in in-hospital mortality rates following IMV.